Debugging on the Shoulders of Giants: Von Neumann's Programs 65 Years Later. - Fagin, Barry; Skrien, Dale (Computer (00189162), 2012)
A study that examined and executed the programs John von Neumann wrote for the IAS machine reveals time-tested truths about computer architecture, side effects, instruction set design, and automatic programming—truths all foreseen by von Neumann and his team more than 50 years ago.